Pulmonary Arterial Remodeling Is Related to the Risk Stratification and Right Ventricular-Pulmonary Arterial Coupling in Patients With Pulmonary Arterial Hypertension - Grignola, Juan C.; Domingo, Enric; López-Meseguer, Manuel; Trujillo, Pedro; Bravo, Carlos; Pérez-Hoyos, Santiago; Roman, Antonio (Frontiers in Physiology, 2021)
Background: Pulmonary arterial (PA) stiffness has an essential contribution to the right ventricular (RV) failure pathogenesis. A comprehensive and multiparameter risk assessment allows predicting mortality and guiding treatment decisions in PA hypertension (PAH). We characterize PA remodeling with intravascular ultrasound (IVUS) in prevalent and stable patients with PAH according to the ESC/ERS risk table and analyze the RV-PA coupling consequences. Methods: Ten control subjects and 20 prevalent PAH adult patients underwent right heart catheterization (RHC) with simultaneous IVUS study. We estimated cardiac index (CI), pulmonary vascular resistance, and compliance (PVR, PAC) by standard formulas. From IVUS and RHC data, PA diameter, wall thickness/luminal diameter ratio, and indexes of stiffness (pulsatility, compliance, distensibility, incremental elastic modulus -Einc-, and the stiffness index b) were measured. We evaluated RV-PA coupling by the ratio of tricuspid annular plane systolic excursion to systolic pulmonary arterial pressure (TAPSE/sPAP). The individual average risk was calculated by assigning a score of 1 (low-risk -LR-), 2 (intermediate-risk -IR-), and 3 (high-risk -HR-) for each of seven variables (functional class, six-minute walking test, brain natriuretic peptide, right atrial area and pressure, CI, and PA oxygen saturation) and rounding the average value to the nearest integer. Results: All PA segments interrogated showed increased vessel diameter, wall cross-sectional area (WCSA), and stiffness in patients with PAH compared to control subjects. 45% were LR, and 55% were IR. Despite the absence of significant PA pressure and PVR differences, the IR group had higher PA stiffness and lower WCSA than LR patients (P <0.05), and it is associated with a lower PAC and TAPSE/sPAP (P < 0.05). The different measurements of PA stiffness showed significant correlations with TAPSE/sPAP (r = 0.6 to 0.76). Conclusion: In prevalent PAH patients, the severity of proximal PA remodeling is related to the simplified risk stratification tool and associated with PAC and RV-PA coupling impairment regardless of the mean PAP. The concomitant assessment of IVUS and hemodynamic parameters at diagnosis and follow-up of PAH patients could be a feasible and safe tool for risk stratification and treatment response of the PA vasculopathy during serial hemodynamic measurements.